Застосування методу двобічних наближень до розв’язання задачі Діріхле для нелінійного рівняння з бігармонічним оператором - Савченко, А. В. (ХНУРЕ, 2023)
The Dirichlet boundary value problem for a nonlinear equation with a biharmonic operator is considered. The considered problem arises when modeling the processes of the theory of elasticity and reflects the deflection of the plate, the ends of which are fixed. For its solution, two-sided approximations methods based on the use of Green’s functions is proposed.
Keywords: метод двобічних наближень; задача Діріхле; нелінійне рівняння; бігармонічний оператор